MODERN ECOPHYSIOLOGY OF WETLANDS: FORMATION OF SUCCESSIONAL CHANGES OF PHYTOCOENOSIS - Hryb, Yosyp; Mykhalchuk, Mykhailo; Volodymyrets, Vitalii; Turchyna, Kateryna (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
Macrophytes form a significant part of the trophic chain in consortia and parcel systems, especially in shallow and upper reservoirs. Calculations show that in addition to physiologically-determined metabolic processes in the system "water environment – bottom sediments – phytomass of higher aquatic vegetation (HAV)" on an order of magnitude intensity of exchange processes is higher. Accordingly, for the stabilization of the ecosystem of the aquatic environment, it is possible to use the censorship of the HAV in the ecologically reasonable limits (in rivers – 10-20%, reservoirs and fish rates 12-15%), the surplus is utilized as a feed in livestock and fish farming or as a component of fertilizers in overgrowing of plants perifiton. Separate groups of higher aquatic vegetation are used as biofuels or wetlands in waterlogged floodplains of rivers to clean up contaminated waters. The study of the peculiarities of the formation of the water environment of small rivers and lakes in the system of ” higher aquatic plants – water”. The possibility of assessing the quality of water by the total mass of dry matter of plants and the necessary increase of it for neutralization of impurities or estimation on the physiological state of acroliths (duckweed) is shown.